An innovative approach to training students of art pedagogical universities - Labunets, Viktor M.; Topchieva Irіna O.; Bondarenko, Anzhelika; Bondarenko, Dmytro; Wei, Liming (Linguistics and Culture Review, 2021)
The distinctive feature of modern musical art is the constant search for new expressive means. Innovations infiltrated all aspects of composition, including the writing technique, understanding of the genre, style, form, and instrumental interpretation. These efforts are aimed at a true diverse and multifaceted embodiment of reality, which is constantly changing due to grand social upheavals. “Creative experiment, inquisitive search, and desire for renewal are inevitable and necessary in modern music. Without these experiments, artistic creativity becomes shallow, declines, and is subjected to sclerotic necrosis”. The growing need for a highly spiritual society requires a rapprochement to teaching and educating the younger generation to develop its spiritual and cultural values, personal and artistic orientations. These trends are primarily related to maintaining and increasing the intellectual and creative potential of a person who can express oneself through professional activities. In this case, the modern socio-cultural stage of development of musical-pedagogical education brings attention to new quality requirements to training of the experts that supposes the necessity and urgency of updating a problem of methodological training of music teachers.